Non-destructive evaluation of bondline defects in honeycomb composite - Chye, Eugene Zong Yi (Nanyang Technological University, 2022)
Honeycomb composites are commonly used as materials for the components of the aircraft. During the honeycomb composites service life, it may experience bondline defects due to stresses and cyclic loadings. Non-destructive testing is usually conducted to check for bondline defects as the testing will not damage the component. However, some bondline defects are inaccessible to test, hence guided wave ultrasonic testing is conducted. This project aims to investigate the effectiveness of using guided wave ultrasonic testing to detect bondline defects in honeycomb composites. Guided wave ultrasonic testing is used as it is able to assess inaccessible areas due to its wave propagation ability. Experiments using guided wave ultrasonic testing would be conducted on a honeycomb composite with fabricated bondline defects. Finite element analysis using 3D models will also be conducted to imitate the experiment set-up and a comparison will be made between the two. While analysing the results, it is noted that defects will tend to display a lower amplitude reading than non-defect areas and the correct frequency is required when conducting guided wave ultrasonic testing. Guided wave ultrasonic testing is suitable to assess for bondline defects in honeycomb composite, however a suitable frequency needs to be chosen.